Family and marriage equality in Perú. A dynamic reading of the 1993 Political Constitution - Rodríguez Campos, Rafael (2017)
The author analyzes, from a constitutional point of view, the recognition and registration of same-sex marriages as a result of a request made to the  corresponding administrative entity.